Impacts of Different Agro-Ecological and Management Practices on the Shrimp Productivity of Ghers in the Southwest Coastal Region of Bangladesh - Huq, KA; Haque, MM; Mazhabuddin, K; Ahmed, SU (Progressive Agriculture, 2014)
The study was undertaken to investigate the impacts of water and soil quality parameters, and management practices on shrimp productivity of ghers in three agro-ecological areas of Paikgacha, Shyamnagar and Rampal in the greater Khulna district of Bangladesh. Five ghers of existing culture systems from each of three locations were selected for this study. Findings revealed that water quality parameters including salinity, alkalinity and dissolved oxygen contributed significantly (p<0.05) and positively to shrimp productivity. Phytoplankton production also showed a positive correlation with shrimp productivity. Soil quality parameters including salinity, potassium and calcium content showed positive correlations with shrimp yield. In relation to management practices, stocking density, sources of PL form natural sources and supplementary feeding showed significant (p<0.05) and positive correlations with shrimp productivity. Water exchange also showed a positive correlation with shrimp yield. DOI: http://dx.doi.org/10.3329/pa.v18i2.18170 Progress. Agric. 18(2): 149 - 155, 2007